Shear bond strength of acid and laser conditioned enamel and dentine to composite resin restorations: An in vitro study - Al Hanouf Al Habdan; Reem Al Rabiah; Riham Al Busayes (Wiley, 2021)
Abstract Objective To compare the shear bond strength of enamel or dentin conditioned with either Er,Cr:YSGG (erbium, chromium: yttrium-scandium-gallium-garnet) laser or phosphoric acid to composite resin restoration. Material and methods Forty posterior human extracted teeth were used. After mesiodistal sectioning of the teeth crowns, the samples were randomly divided into two groups-in the first group (E), bonding was performed on the enamel after roughening and in the second group (D), the enamel was removed and bonding was performed on the dentin. These groups were further randomly divided into two subgroups according to the type of etching (n = 20 each). In the acid‐etched groups (EA and DA), the surfaces were etched with 37% phosphoric acid. In the laser‐conditioned groups (EL and DL), the surfaces were conditioned with Er,Cr:YSGG laser. Total‐etch adhesive system was used to bond all the 80 specimens resin composite. The composite was vertically light‐cured, and the specimens were subjected to a shear bond strength test. Modes of bond failure were determined with a stereomicroscope. Results The highest shear bond strength was observed for the DA group (16.25 ± 1.10 MPa, p < 0.0001), whereas the lowest was observed for the DL group (8.56 ± 0.67 MPa). The adhesive failure mode was the most frequently observed in all groups. Conclusions The shear bond strength of composite resin bonded to enamel and dentin etched with phosphoric acid was higher than when conditioned with Er,Cr:YSGG laser. Thus, laser conditioning is not recommended.